Tenascin‐C is increased in atherothrombotic stroke patients and has an anti‐inflammatory effect in the human carotid artery. (14th May 2014) - Clancy, Paula; Lincz, Lisa F.; Maguire, Jane; McEvoy, Mark; Koblar, Simon A.; Golledge, Jonathan
Abstract Tenascin‐C (Tn‐C) is an endogenous ligand of toll‐like receptor‐4 (TLR‐4); a key signalling molecule associated with chronic inflammatory conditions. Both Tn‐C and TLR‐4 are increased in unstable human atheroma, but their effects on local inflammatory conditions have not been investigated. The aim of the present study was to investigate the association and functional implications of Tn‐C/TLR‐4 signalling in large artery atherosclerotic stroke. Plasma Tn‐C was measured by ELISA and found to be higher in recent stroke patients (n = 336; median 12.77 µg/mL, inter‐quartile range 10.23–15.74 µg/mL) than in controls (n = 321; median 11.31 µg/mL, inter‐quartile range 8.89–13.90 µg/mL), P < 0.001. Plasma Tn‐C was also independently positively associated with stroke (odds ratio for highest Tn‐C quartile 2.27, 95% confidence interval 1.37–3.76). Assessment of Tn‐C associated chronic cytokine secretion was performed in vitro using paired, human, macroscopically disease matched, carotid atheroma tissue biopsies obtained from five patients undergoing carotid endarterectomy. A 4‐day incubation with specific Tn‐C blocking antibodies (Abs) increased secretion of TLR‐4‐associated cytokines, interleukin (IL)‐8, IL‐1β, tumour necrosis factor and C‐C motif chemokine (CCL)3 and expression of TLR‐4 in the tissue. These results suggest with Tn‐C blockade another endogenous TLR‐4 ligand upregulates TLR‐4 expression and subsequent cytokine secretion. Titration of the Tn‐C Abs also dose dependently increased secretion of IL‐6, IL‐8, IL‐1β, and CCL3 in mixed, healthy, primary vascular cell culture. In summary, circulating concentrations of Tn‐C are higher in patients with a recent history of atherosclerotic stroke and may play an anti‐inflammatory role by reducing pro‐inflammatory cytokine release from atheroma. © 2014 BioFactors, 40(4):448–457, 2014